Evaluation of the Antimicrobial Activity and Chemical Composition of the Leaf Extract of Annona muricata Linn (Soursop) Grown in Eastern Nigeria - , Rosemary I. Uchegbu; , Kalu U. Ukpai; , Irenus C. Iwu; , Jacinta N. Akalazu (Archives of Current Research International, 2017)
Aim: This work was carried out to test the inhibitory ability of the plant extract on some human pathogens, to identify the fungi associated with yam tuber rot in Nigeria, to evaluate the antifungal activity of methanol extract of Annona muricata (30 mg/ml) leaf along with mancozeb (0.3 g/ml on mycelial growth inhibition of fungi isolated from Dioscorea rotundata (poir) (white yam) and to determine the phytochemicals and nutritive values of Annona muricata leaf. Study Design: The study was designed to test the inhibitory ability of the extract on human and plant pathogens, to determine the phytochemicals and nutritive values of Annona muricata leaf. Place and Duration of Study: Department of Chemistry, Alvan Ikoku Federal College of Education, Owerri and Department of Plant Science and Biotechnology, Imo State University, Owerri, Nigeria during February to July 2016. Methodology: Standard assay techniques were used to evaluate the leaves for nutrients and phytochemical composition. The antibacterial activity was performed by filter paper disc diffusion technique. Antifungal susceptibility test against the fungal isolates were performed by disc diffusion method. Results: The ethanol extract inhibited all the tested organisms E. coli, K. pneumoniae, S. aureus, P. mirabilisand Salmonella. The antifungal results showed that Aspergillus flavus, Fusarium oxysporium, Rhizopus stolonifer and Botryodiploidia theobromae were associated with yam tuber rot. The results revealed that Annona muricata inhibited the growth of the test organisms with different inhibition zones. The most devastating fungus was B. theobromae, causing rot of 9.50 cm2, this was followed by R. stolonifer, causing rot of 7.50 cm2 while the least devastating was F. oxysporium (7.31 cm2). In vivo results showed that Annona muricata leaf extract was effective in reducing the yam tuber rot. The phytochemical studies of Annona muricata revealed the presence of alkaloids (1.66%), flavonoids (1.15%), tannins (0.75%), phenols (0.14%) and saponins (2.15%). The leaves contain some minerals such as calcium (Ca) (3.87 %), magnesium (Mg) (1.07%), potassium (K) (0.30%), sodium, (Na) (0.26%), phosphorus (P) (0.30%) and nitrogen,(N) (3.89%). The plant samples were found to be rich in vitamins comprising riboflavin (0.11 mg/100g), thiamin (0.15 mg/ 100 g), niacin (0.25 mg/ 100 g) and ascorbic acid (8.20 mg/ 100 g). The proximate composition revealed the presence of protein (24.3%), crude fibre (6.17%), fats/oil (2.52%), ash (5.30%), carbohydrates (61.7%) and food energy (366.7 g/cal). The leaves contain appreciable quantities of proteins, fiber, vitamins and minerals which have health promoting benefits. The results of the analysis justify the use of Annona muricata as a good food and a potent drug.